Universal COVID-19 screening of 4040 health care workers in a resource-limited setting: an Egyptian pilot model in a university with 12 public hospitals and medical centers. (23rd October 2020) - Mostafa, Aya; Kandil, Sahar; El-Sayed, Manal H; Girgis, Samia; Hafez, Hala; Yosef, Mostafa; Saber, Saly; Ezzelarab, Hoda; Ramadan, Marwa; Afifi, Iman; Hassan, Fatmaelzahra; Elsayed, Shaimaa; et al.
Abstract: Background: The scale of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection among health care workers (HCWs), particularly in resource-limited settings, remains unclear. To address this concern, universal (non-symptom-based) screening of HCWs was piloted to determine the proportion of SARS-CoV-2 infection and the associated epidemiological and clinical risk factors at a large public health care facility in Egypt. Methods: Baseline voluntary screening of 4040 HCWs took place between 22 April and 14 May 2020 at 12 hospitals and medical centres in Cairo. Epidemiological and clinical data were collected using an online survey. All participants were tested for SARS-CoV-2 using reverse transcription polymerase chain reaction (RT-PCR) and rapid IgM and IgG serological tests. Results: Of the 4040 HCWs screened, 170 [4.2%; 95% confidence interval (CI): 3.6-4.9] tested positive for SARS-CoV-2 by either of the three tests (i.e. infected); 125/170 (73.5%) tested PCR-positive. Most infected HCWs were nurses (97/170, 57.5%). Median age of infected HCWs was 31.5 [interquartile range (IQR): 27.0–41.3] years. Of infected HCWs, 78 (45.9%) reported contact with a suspected case and 47 (27.6%) reported face-to-face contact within 2 m with a confirmed case. The proportion of infection among symptomatic HCWs ( n = 54/616) was 8.8% (95% CI: 6.7-11.3); 6/54 (11.1%) had fever ≥38°C and 7/54 (13.0%) reported severe symptoms. Most infected HCWs were asymptomatic (116/170, 68.2%). The proportion of infection among asymptomatic HCWs ( n = 116/3424) was 3.4% (95% CI: 2.8-4.0). Conclusions: The high rate of asymptomatic infections among HCWs reinforces the need for expanding universal regular testing. The infection rate among symptomatic HCWs in this study is comparable with the national rate detected through symptom-based testing. This suggests that infections among HCWs may reflect community rather than nosocomial transmission during the early phase of the COVID-19 epidemic in Egypt.